Adherence to diagnosis followed by selective treatment of schistosomiasis mansoni and related knowledge among schoolchildren in an endemic area of Minas Gerais, Brazil, prior to and after the implementation of educational actions. (May 2021) - Favre, Tereza Cristina; Massara, Cristiano Lara; Beck, Lilian Christina Nóbrega Holsbach; Cabello, Rocío Karina Saavedra Acero; Pieri, Otavio Sarmento
Abstract: Introduction: Brazilian guidelines for schistosomiasis elimination recommend regular search of infection carriers and their timely treatment. This study evaluates the effect of educational actions (EAs) among schoolchildren on adherence to diagnosis and treatment, as well as on knowledge of the disease. Methods: In April/2013, a questionnaire was applied to 6th-to-8th-grade pupils of eight public schools to evaluate prior knowledge of disease and self-reported risk behavior. Baseline parasitological survey (PS) was done in May/2013, followed by selective treatment and cure assessment. The schools were then randomly allocated to experimental (EG) and control (CG) groups, with and without EAs, respectively. EAs were conducted for 3 months from August/2013. Questionnaire was reapplied in November/2013, April/2014, October/2014, and October/2015 to evaluate changes in knowledge about the disease and self-reported risk behavior. Two further annual PSs (May/2014 and May/2015), each followed by treatment of positives, allowed to evaluate between-group differences and intra-group changes in adherence to diagnosis and treatment, and to follow-up prevalence and intensity of infection. Results: Adherence to diagnosis did not differ significantly between EG (84.1%) and CG (81.1%) at baseline but was significantly higher in EG in subsequent PSs. Overall, adherence to treatment was higher than 90% in all three PSs; cure was 98.4%, egg-reduction was 99.8% and reinfection, 2.8%. Prevalence fell significantly in EC (from 23.5% to 6.8%) and CG (from 21.8% to 2.4%), the same occurring with intensity (from 54.2 to 4.6 epg in EG and from 38.4 to 1.3 epg in CG). Disease knowledge increased significantly in EG and CG; knowledge about disease transmission increased significantly more in the EG. Self-reported risk behavior remained above 67% and did not differ significantly between EG and CG. Conclusion: EAs increased adherence of schoolchildren and improved knowledge about the disease, confirming that EAs are an important tool to enhance schoolchildren participation in control campaigns. Highlights: Educational actions improved adherence to stool testing. Disease knowledge also improved with educational actions. Risk behavior stayed high despite educational actions.